Problems and Countermeasures on the Fishery Development in the South China Sea* - Hu Zhang (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2016)
The South China Sea is one of the most abundant fishery areas in the world, which is a typical multi fish species area. The South China Sea Fisheries can be divided into four parts, the northern continental shelf offshore fisheries, Xisha Qundao, Zhongsha Qundao and Nansha Qundao coral reef fisheries, the northern slope fisheries and Southern Ocean, rising flow fisheries. In recent years, the ecological environment of the South China Sea has been severely damaged, resulting in the fisheries resources becoming poor increasingly, in the meantime, there exist other problems, such as the effect and validity of unilateral management of the fishery resources is still limited, bilateral and multilateral cooperation are not yet mature. Therefore, to strengthen the multilateral cooperation is the effective way for the development of fishery resources in the South China Sea. In order to avoid disputes, as a large marine ecosystem, the South China Sea with the ecosystem approach as a guide for cooperation, while carrying on the multilateral cooperation, shall keep in line with the characteristics of the fisheries resources. In the process of practical cooperation, we shall conclude the multilateral cooperation treaty, implement the fishing dynamic monitoring system in the South China Sea, establish the conservation organizations on fishery cooperation and promote the development of leisure fishery in South China Sea vigorously.